Nanodrug‐Engineered Exosomes Achieve a Jointly Dual‐Pathway Inhibition on Cuproptosis - Hanxiao Sun; Yang Zou; Zhengtai Chen; Yan He; Kai Ye; Huan Liu; Lihong Qiu; Yufan Zhang; Yuexue Mai; Xinghong Chen; Zhengwei Mao; Wei Wang; et al. (Advanced Science)
Abstract Cuproptosis, caused by an intracellular overload of copper (Cu) ions and overexpression of ferredoxin 1 (FDX1), is identified for its regulatory role in the skin wound healing process. This study verifies the presence of cuproptosis in skin wound beds and reactive oxygen species‐induced cells model. To address the two pathways leading to cell cuproptosis, a nanodrug‐engineered exosomes is proposed. A Cu‐chelator (Clioquinol, CQ) polydopamine (PDA)‐modified stem cell exosome loaded with siRNA‐FDX1, named EXOsiFDX1‐PDA@CQ, is designed to efficiently inhibit the two cuproptosis pathways. The functionalized exosomes are loaded into an injectable hydrogel and applied to treat diabetic wounds in mice and acute skin wounds in pigs. The local and controlled release of EXOsiFDX1‐PDA@CQ ensures the retention of the therapeutic agent at wound beds, effectively promoting wound healing. The strategy of engineered exosomes with functional nanoparticles (NPs) proposed in this study offers an efficient and scalable new approach for regulating cuproptosis.